The impact of governmental consumer spending on the development of the current account balance in Iraq for the period (1990-2014) using ARDL model - البيرماني, صلاح مهدي; داود, محمد نوري (Journal of Economics and Administrative Sciences, 2018)
To avoid the negative effects due to inflexibility of the domestic production inresponse to the increase in government consumption expenditure leads to more  imports to meet the increase in domestic demand resulting from the increase in government consumption expenditure. Since the Iraqi economy economy yield unilateral depends on oil revenues to finance spending, and the fact government consumer spending is a progressive high flexibility the increase in overall revenues, while being a regressive flexibility is very low in the event of reduced public revenues, and therefore lead to a deficit in the current account position. And that caused the deficit for imbalance are the disruption of the structure of government spending in favor of consumer spending and the disruption of the current account structure, as the export of a single commodity is oil from which to finance the spending offset by a wide range of imports that are brought to a large portion of this spending it.Therefore research aims to determine the impact of government consumer spending on the development of the current account balance in light of increased government spending, through the reality of government consumer spending analysis and structure of the current account in Iraq, measure and analyze the impact of government consumer spending on the development of the current account balance during the study period (1990- 2014), has been using Autoregressive Distributed Lag Model(ARDL), because of this form of advantages is the suitability for small samples and data of stationtary in the first-difference or the level or a combination of the two, a researcher has reached to the existence of a long-term positive relationship between spending government consumption and the deficit current account balance, as the increase in government consumption expenditure (1%) lead to increased current account deficit by (0.25%). The increase in consumer spending, the government and one unit (million I.D) has led to the increase of imports of goods and services by (0.58) unit (million I.D) in the short term and by (1.16) (million I.D) in the long term.